1995
DOI: 10.1159/000098781
|View full text |Cite
|
Sign up to set email alerts
|

Thalamotomy and Caudatotomy with the Gamma Knife as a Treatment for Parkinsonism with a Comment on Lesion Sizes

Abstract: Radiosurgery with the Gamma Knife was performed in 12 patients with parkinsonism. In 9 patients small lesions were created in the head of the caudate nucleus bilaterally. Two patients underwent radiosurgical thalamotomy, and 1 patient was treated with caudatotomy and thalamotomy. After a follow-up period of 1–12 months, 9 patients of the caudatotomy group and all patients with thalamotomies showed clear benefit. There was no complication or side effect that could be related to the treatment. Pre- and postopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…1). The authors of several studies have reported success rates in tremor control in patients with PD, essential tremor, and tremor related to multiple sclerosis or other causes 13,17,41,42,43,51,68,69,72 that are comparable to those achieved using other methods. Complications are usually rare, mild, and temporary, although unusual complications 62 and severe, permanent complications 47 have also been reported.…”
Section: Treatment Of Tremorsmentioning
confidence: 91%
“…1). The authors of several studies have reported success rates in tremor control in patients with PD, essential tremor, and tremor related to multiple sclerosis or other causes 13,17,41,42,43,51,68,69,72 that are comparable to those achieved using other methods. Complications are usually rare, mild, and temporary, although unusual complications 62 and severe, permanent complications 47 have also been reported.…”
Section: Treatment Of Tremorsmentioning
confidence: 91%
“…reported an experience of radiosurgical thalamotomy (n=3) and caudatotomy (n=10), with clinical improvement in most patients and no morbidity. [8]…”
Section: Radiosurgical Thalamotomymentioning
confidence: 99%
“…In 1991, Lindquist et al [7] reported 2 cases of Gamma Knife thalamotomy with good relief of tremor in one and partial relief in other [7]. Friehs et al [8] reported a good response at 3-4 weeks in all 3 patients treated using a single 4-mm collimator with a maximum dose of 160 Gy. Duma et al [9] performed 38 thalamotomies for parkinsonian tremor using the Gamma Knife unit and reported complete elimination in 24%, excellent relief in 26% and good improvement in 31% of the patients.…”
Section: Gamma Knife Thalamotomymentioning
confidence: 99%